ETHNOMATHEMATIC STUDY: NUMBER SYSTEM AND CULTURAL MEANING IN THE SASAK TRIBE COMMUNITY - Fauzi, Lalu Muhammad; Ahyan, Shahibul; Rasidi, Ahmad; Wardi, Zaotul; Gazali, Muhammad (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2023)
The uniqueness and cultural diversity of traditional communities as reflected in ideas, activities and artifacts can be studied and used as a source of learning mathematics. Most people view that mathematics is not related to culture or is culturally independent. The development of mathematics in society through cultural activities can be studied through ethnomathematics studies that can bring mathematics closer to student culture. Thus, this study aims to explore the number system and cultural meaning that developed in the Sasak people which can be used as a source of learning mathematics on the island of Lombok. This research is a research with ethnographic method. Research data was collected through observation, literature study, and interviews with cultural practitioners, traditional chief leaders, traditional leaders, Sasak cultural researchers and humanists. The results of this study indicate that the development of the number system has been developing for a long time in the Sasak people. Counting activities (bejinah) use arithmetic operations as is done in general but with local terms, namely total (rombok), less (sedik), times (kali) and divide (bagi). The developing number system is understood as a number in quantitative and qualitative form, in unit or set numbers. There are 5 types of unit or set numbers known by the Sasak people, namely bond units, measuring units for solid objects, measuring units for liquid objects, area units and length units. The mathematical concepts found in the activities of the Sasak people can be used as a source of learning and as a starting point in learning mathematics